2018
DOI: 10.1089/scd.2017.0241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibacterial and Immunological Properties of Mesenchymal Stem/Stromal Cells from Equine Bone Marrow, Endometrium, and Adipose Tissue

Abstract: Equine mesenchymal stem/stromal cells (MSCs) are multipotent cells that are widely used for treatment of musculoskeletal injuries, and there is significant interest in expanding their application to nonorthopedic conditions. MSCs possess antibacterial and immunomodulatory properties that may be relevant for combating infection; however, comparative studies using MSCs from different origins have not been carried out in the horse, and this was the focus of this study. Our results showed that MSC-conditioned medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 42 publications
(51 reference statements)
1
42
0
Order By: Relevance
“…Flow cytometry has been used to characterise C. gigas hemocytes, demonstrating this approach can be applied to molluscan cells (Jiang et al, 2016). In experimentally challenging mammalian cells clusters of differentiation and qPCR can be used to characterise a population of cells (Cortes et al, 2018). These approaches have not been developed in molluscan culture, making it difficult to determine what cell types have been cultured beyond morphological characterisation.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry has been used to characterise C. gigas hemocytes, demonstrating this approach can be applied to molluscan cells (Jiang et al, 2016). In experimentally challenging mammalian cells clusters of differentiation and qPCR can be used to characterise a population of cells (Cortes et al, 2018). These approaches have not been developed in molluscan culture, making it difficult to determine what cell types have been cultured beyond morphological characterisation.…”
Section: Discussionmentioning
confidence: 99%
“…Little is currently known about the precise mechanism underlying the antibacterial effects of MSCs. Recent data suggest that MSCs exert strong antimicrobial effects through indirect and direct mechanisms: indirectly, through their role in the host immune response against pathogens, especially in the dynamic coordination of the immune system [ 33 , 34 , 35 , 36 ] or by increasing the activity of phagocytes [ 6 , 32 , 37 , 38 ]; and directly, through the secretion of antimicrobial peptides and proteins (AMPs) [ 1 , 5 , 6 , 7 , 8 ]. Moreover, MSCs have been found to release circular membrane fragments called microvesicles (MVs), containing numerous proteins, mRNAs, microRNAs, organelles and lipids involved in cell-cell communication and the transfer of cellular material.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculate that this effect can be explained by the call of neutrophils within the vascular compartment mediated by IL-10 (68). Equine MSCs from different tissue are able to express some immunomodulatory genes such as monocyte chemoattractant protein-1 (MCP-1), interleukin-6 (IL-6), interleukin-8 (IL-8), and chemokine ligand-5 (CCL5), suggesting that respective cytokines may help limit infection indirectly by recruiting and activating immune cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…have antimicrobial properties (17)(18)(19). Studies using models of infection-induced organ damage have shown that MSCs can exhibit antibacterial properties by the release of soluble molecules, such as the peptides catelicidine LL-37 (20) and lipocalin-2 (21), which lead to the clearance of bacteria.…”
Section: Introductionmentioning
confidence: 99%